Overview of the Level of Knowledge of Pregnant Women About Antenatal Care in the Working Area of the Sititio Health Center - Manggala Putra Gultom (Publikasi Indonesia, 2024)
This study aims to describe the level of knowledge of pregnant women about antenatal care (ANC) services in the working area of the Sitiotio Health Center, Samosir Regency. ANC is an essential health service for pregnant women to reduce maternal and fetal mortality rates, which is one of the global targets in the Sustainable Development Goals (SDGs). This study uses a descriptive design with a cross-sectional approach, involving 50 respondents who are selected through the total sampling technique. Data collection was carried out using questionnaires, and data analysis was carried out univariate using SPSS. The results showed that 27 pregnant women (54%) had sufficient knowledge, 13 (26%) had less knowledge, and 10 (20%) had good knowledge. Good knowledge of ANC is important to improve maternal and fetal health and reduce morbidity and mortality rates. This study provides recommendations to improve health counseling for pregnant women to strengthen their understanding of ANC.